Київський список «Подорожі патріарха Макарія» - Петрова, Ю.І. (Український історичний журнал, 2013)
Ідеться про невідомий в європейській науці поза межами України скорочений
арабомовний список діаріушу Павла Алеппського про подорож антіохійського
патріарха Макарія III православними країнами у XVII ст., який зберігається в
Києві й чекає на наукове дослідження та публікацію. Наведено основні відомості
про рукопис, його списки, історію дослідження. Окремо виділено внесок Т.Кезми
та О.Пріцака, які перекладали Київський список. Окреслено перспективи дослідження
рукопису в межах міжнародного проекту з видання повного критичного тексту «Подорожі». The publication deals with the unknown to the European scientific community
outside Ukraine abridged copy of Paul of Aleppo’s diary in Arabic about the
journey of Macarius III Patriarch of Antioch through Orthodox countries in the
17th century, which is preserved in Kyiv and is to be examined and published. The
main information concerning the manuscript, its copies and history of its research
is given, with special attention to the contribution of T.Kezma and O.Pritsak, who
translated the copy preserved in Kyiv. Perspectives of the manuscript research in
the framework of the international project for edition of the full critical text of the “Travels” are outlined.